Efectiveness of 0,05% sodium hypochlorite rinse against gingival inflammation - Encalada Abad, Carolina (2017)
Objectives: To compare the effectiveness of a mouth rinse of sodium hypochlorite 0.05% and 0.12% chlorhexidine against supragingival plaque and gingivitis development. Materials and Methods: A comparative randomized, double blind parallel group trial was performed with 38 young men who form part of the Ecuadorian Military Service. Subjects were divided into two groups according to their hygiene methods and each group receives a type of blinded rinse, after a professional cleaning. The rinses were indicated twice a day with rinses of Sodium Hypochlorite administered to Group 1 and 0,12% Chlorhexidine administered to Group 2, using 15 ml of the substances twice a day during 60 seconds for 21 days. Plaque index (QHPI), Löe and Silness Gingival Index, and Percentage of bleeding sites on probing were recorded on Day 0 and Day 21. Adverse effects were evaluated with questionnaires and pictures were taken in order to register any staining. Results: Values between groups showed no statistically significant differences. On day 21, the plaque indexes decreased in both groups. The CLX group, the average QHPI values decreased 0.38, in the NaOCl group the average values decreased 0.12. The average value in the CLX IG group decreased 0.42 and 0.38 in the NaOCl group. The percentage of sites that bled on probing decreased 3.84% in average in the CLX group and 7.07% in the NaOCl group. Conclusions: Clorhexidine has evidence of "Gold Standard Agent" in terms of antiplaque and antigingivitis, but mouth rinses with 0.05% NaOCl were effective compared to chlorhexidine in terms of antimicrobial action, which could be an effective method to treat inflammation gingival and the accumulation of bacterial plaque at a lower cost.